2012
DOI: 10.1007/s13197-011-0600-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of technological parameters for preparation of lycopene microcapsules

Abstract: Lycopene belongs to the carotenoid family with high degree of unsaturation and all-trans form. Lycopene is easy to isomerize and auto oxide by heat, light, oxygen and different food matrices. With an increasing understanding of the health benefit of lycopene, to enhance stability and bioavailability of lycopene, ultrasonic emulsification was used to prepare lycopene microcapsules in this article. The results optimized by response surface methodology (RSM) for microcapsules consisted of four major steps: (1) 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Various packaging techniques have been proposed to increase fruit post-harvest stability and quality. [6,7] Furthermore, encapsulation may allow for carotenoid dispersion in water, thus enabling their application in a wider range of products. [8] Spray drying stands out as one of the most widely used microencapsulation techniques because of apparatus availability, the ability to apply multiple encapsulating agents, good volatile compound retention, and final product stability.…”
Section: Introductionmentioning
confidence: 99%
“…Various packaging techniques have been proposed to increase fruit post-harvest stability and quality. [6,7] Furthermore, encapsulation may allow for carotenoid dispersion in water, thus enabling their application in a wider range of products. [8] Spray drying stands out as one of the most widely used microencapsulation techniques because of apparatus availability, the ability to apply multiple encapsulating agents, good volatile compound retention, and final product stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, as other carotenoids, it is water insoluble, and only slightly soluble in oil, that makes it problematic to be used in many food and pharmaceutical formulations. Additionally, it is prone to light, heat and oxygen, which restrictions furthermore its applications in pharmaceutical, nutraceutical and food products (Guo et al 2014;Tan and Nakajima 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Then, one of the important factors for making nanoparticles is the selection of stabilizer system. It has been shown that mixtures of stabilizers can improve the physicochemical properties of nanoparticles, more efficient than using them individually (Anarjan and Tan 2013b;Guo et al 2014;Sen Gupta and Ghosh 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, contents of other pigment members of the carotenoid family, such as lycopene, zeaxanthin, β-cryptox- anthin, and β-carotene, were not detected using this method, possibly due to the auto-oxidation effects during the preparation process. 15 We and others found that the cell size of subcutaneous adipocytes is much larger than that of OF cells. In our present study, the histological results were consistent with this previous finding (Figure 1b−e), indicating that OF contains smaller intracellular LDs than SF.…”
Section: ■ Discussionmentioning
confidence: 83%
“…Our results showed that the concentration of lutein per mg of OF was significantly lower than that of SF (Figure f,g), which might be a major factor contributing to the color difference between OF and SF. Unfortunately, contents of other pigment members of the carotenoid family, such as lycopene, zeaxanthin, β-cryptoxanthin, and β-carotene, were not detected using this method, possibly due to the auto-oxidation effects during the preparation process …”
Section: Discussionmentioning
confidence: 99%